Efficient Pyrazole Moiety‐Containing Ligands for Cu‐Catalyzed O‐Arylation of Phenols. Issue 14 (8th April 2020) - Zhao, Yingying; Wang, Xiangyong; Kaneyama, Ryo; Kodama, Koichi; Hirose, Takuji
Abstract: Seven pyrazole‐ or pyridine‐containing N2 ‐ and N3 ‐ligalitnds (L1 –L7 ) were developed for the ligand‐assisted CuI‐catalyzed coupling reactions of aryl halides with phenols. The structural and electronic effects were studied for various combinations of pyridine and/or imine nitrogen binding sites in the ligands. Screening their abilities showed most of them to be better than 4, 4'‐dimethoxybipyridine (L8 ). Among them, 2‐(1‐pyrazolyl)pyridine (L1 ) featuring two types of binding sites gave the best results, with yields of up to 95% at 100 °C at a catalyst loading of 10 mol% (CuI/L in 1 : 1 ratio). Free radical scavengers, 2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO) (1.0 eq.) and cumene (1.0 eq.), lowered the yields by more than half, but the reaction was not completely quenched even when 3.0 eq. of TEMPO was used. A non‐radical and a radical mechanisms, are proposed for the L1 ‐promoted coupling reaction, well explained the experiments results. In addition, the structure of the catalyst species were elucidated through single crystal XRD and DFT (density functional theory) calculations. Abstract : Among seven new N2 ‐ and N3 ‐ligands, 2‐(1‐pyrazolyl)pyridine (L1) having two types of coordinating sites gave the best results up to 95% yield for Cu‐catalyzed coupling between aryl halides and phenols using 10 mol% CuI⋅L1 at 100 °C. Its Cu complex catalyst structure was suggested from the dimeric crystal structure and its reactivity.